2021
DOI: 10.1002/chem.202100645
|View full text |Cite
|
Sign up to set email alerts
|

Energetics of Competing Chiral Supramolecular Polymers

Abstract: Chirality can have unexpected consequences including on properties other than spectroscopic. We show herein that a racemic mixture of bis‐urea stereoisomers forms thermodynamically stable supramolecular polymers that result in a more viscous solution than for the pure stereoisomer. The origin of this macroscopic property was probed by characterizing the structure and stability of the assemblies. Both racemic and non‐racemic bis‐urea stereoisomers form two competing helical supramolecular polymers in solution: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…[47,48] The extent of the S&S effect is correlated to the number of defects, as quantified by the energetic values associated with helix reversals and chiral mismatches. [49,50] Aggregation of hydrogen-bonded helical structures by complementary interactions has been exploited to construct hierarchical [39,40,[51][52][53] or competitive [54] supramolecular aggregates with tunable chiroptical properties. The orthogonality of hydrogen bonding and metal-ligand interactions also allowed the construction of crosslinked supramolecular polymer networks, yet the impact of chirality was not probed in this system.…”
Section: Introductionmentioning
confidence: 99%
“…[47,48] The extent of the S&S effect is correlated to the number of defects, as quantified by the energetic values associated with helix reversals and chiral mismatches. [49,50] Aggregation of hydrogen-bonded helical structures by complementary interactions has been exploited to construct hierarchical [39,40,[51][52][53] or competitive [54] supramolecular aggregates with tunable chiroptical properties. The orthogonality of hydrogen bonding and metal-ligand interactions also allowed the construction of crosslinked supramolecular polymer networks, yet the impact of chirality was not probed in this system.…”
Section: Introductionmentioning
confidence: 99%
“…19(d) and (e)). 91 In this work, they found the existence of two competing helical assemblies, a double helical and a single helical one depending on the temperature. The discrimination between both types of assemblies was assessed by CD spectroscopy, small angle neutron scattering (SANS) and nanodifferential scanning calorimetry (nDSC).…”
Section: Amplification Of Asymmetry: Moving Forward With Controlled S...mentioning
confidence: 75%
“…Chiral nanoarchitectures have attracted substantial interest due to a broad range of possible applications, while there has been growing adoption of chiral self-sorting for the design of switchable and metastable supramolecular structures. For example, Shang et al reported that a mixture of Zn 2+ cations with a chiral naphthalene diimide ligand containing alanine termini forms homochiral and heterochiral coordination polymers, enabling enantioselective sensing of hazardous amines and naproxen (a nonsteroidal anti-inflammatory drug) based on fluorescence and chemoresistive variations . Hecht et al reported the self-assembly of a core-twisted perylene bisimide into a homochiral columnar mesophase when a solution of the monomer is slowly cooled, while the same molecule forms heterochiral lamellar liquid crystals when rapidly cooled based on kinetically controlled chiral self-sorting.…”
Section: Introductionmentioning
confidence: 99%